1988
DOI: 10.1104/pp.87.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Biogenesis 60

Abstract: In higher plants, most Photobiology, ABL, University of Illinois, Urbana, monocarboxylic biosynthetic route is not as preponderant as the DV monocarboxylic route, the DV and MV monocarboxylic routes were found to be weakly interconnected (15,17). From in vitro investigations, the DV and MV monocarboxylic routes did not appear to be interconnected at the level of Pchlide, either in etiolated barley or in etiolated cucumber (15,17). Indeed, although it is firmly believed that DV Pchlide is convertible to MV Pc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 5 publications
1
26
0
Order By: Relevance
“…By using an in vivo method with isolated cucumber etioplast membranes, Parham and Rebeiz (1995) also report that DV-Chlide a can be readily converted to MV-Chlide. The rate of this conversion is estimated to be 50-to 300-fold higher than that of the activity to convert DV-Pchlide to MV-Pchlide in isolated barley etioplasts (Tripathy and Rebeiz 1988). Although the activity within cucumber and barley etioplasts in these experiments cannot be directly compared, these results are consistent with the hypothesis that DVR prefers DV-Chlide to DV-Pchlide.…”
Section: 8-divinyl Pchlide a 8-vinyl Reductasesupporting
confidence: 80%
“…By using an in vivo method with isolated cucumber etioplast membranes, Parham and Rebeiz (1995) also report that DV-Chlide a can be readily converted to MV-Chlide. The rate of this conversion is estimated to be 50-to 300-fold higher than that of the activity to convert DV-Pchlide to MV-Pchlide in isolated barley etioplasts (Tripathy and Rebeiz 1988). Although the activity within cucumber and barley etioplasts in these experiments cannot be directly compared, these results are consistent with the hypothesis that DVR prefers DV-Chlide to DV-Pchlide.…”
Section: 8-divinyl Pchlide a 8-vinyl Reductasesupporting
confidence: 80%
“…The polyethylene-column HPLC used in this study is par (11). The contents of DV-Pchlide in leaf mustard and cucumber are strongly dependent on their age and decrease rapidly as shown below (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tripathy and Rebeiz (10) reported that in higher plants, MV-and DV-Pchlides were formed from MV-and DV-protoporphyrin via MV-and DV-monocarboxylic biosynthetic routes, respectively. They also described four types of greening groups in higher plants on the basis of MV-or DV-monocarboxylic biosynthetic routes that predominate at night or in daylight (11 All plants seeds were purchased from a local market. Seeds of each plant were germinated in wet cotton at 250C in the dark for 1 to 10 d.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that divinyl chlorophyllide was efficiently converted to monovinyl chlorophyllide by membrane fraction from cucumber (Parham and Rebeiz, 1992), whereas divinyl protochlorophyllide was not. Another report indicated that the 8-vinyl group of protochlorophyllide was reduced by intact chloroplasts (Tripathy and Rebeiz, 1988). These reports indicated that there are multiple enzymes for the vinyl reduction.…”
Section: Dvr Encodes 38-divinyl Protochlorophyllide a 8-vinyl Reductasementioning
confidence: 97%